O2 distribution and dynamics in the rhizosphere of Phragmites australis, and implications for nutrient removal in sediments. (15th October 2021) - Li, Cai; Ding, Shiming; Ma, Xin; Chen, Musong; Zhong, Zhilin; Zhang, Yi; Ren, Mingyi; Zhang, Min; Yang, Liyuan; Rong, Nan; Wang, Yan
Abstract: Root-triggered microscale variations in O2 distribution in the rhizosphere of young Phragmites australis are important for nutrient removal in sediments. In this study, the micro-scale O2 dynamics and the small-scale changes of soluble reactive phosphorus (SRP) and ammonium (NH4 + ) in the rhizosphere of P. australis were investigated using planar optodes and high-resolution dialysis (HR-Peeper), respectively. Results suggested that root O2 leakage has a highly variable distribution depending on the stage of root growth, the site of O2 leakage gradually shift from the entire emerging main roots to the main root tip and subsequently shifted the emerging lateral roots. The O2 concentration increased in the rhizosphere with increasing light intensity and O2 levels in the overlying water. Continuous O2 release from the lateral roots causes the formation of iron plaque on the surface of lateral roots, which reduce the mobility of P by adsorption of iron plaque in the rhizosphere. The oscillation of oxic-anoxic root zones improves nitrogen removal through the processes of anammox, heterotrophic denitrification and nitrification. This work from the micro-scale demonstrates that the O2 concentration is the spatio-temporal variations in the rhizosphere, and it presents an important role for nutrient removal in sediments. Graphical abstract: Image 1 Highlights: Micro-scale O2 dynamics in the rhizosphere of P. australis was studied by planar optode. Radial O2 loss was highly spatio-temporal dynamic as the roots grow. Radial O2 loss was associated with irradiance and O2 level in the overlying water. The nutrient reduction in the rhizosphere attribute to the radial O2 loss. Abstract : O2 release from the lateral roots contributed to the oxidizing environment in the rhizosphere of P. australis, and supported the removal of excess nutrients in sediments.